Acute fatty liver of pregnancy in a young adult woman - Yaneida Machado Quiala; Osiel Mauricio Lobaina Rosales; Yailenys Ortiz Brizuela (Centro Provincial de Información de Ciencias Médicas, 2023)
The case report of a 20 years pregnant woman is presented, who went to the maternal block emergency room of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba due to run-down, nausea and diffuse discomfort. During the physical exploration sweaty and cold skin, tachycardia and jaundice were found. Diverse complementary exams were carried out and a hepatic disorder was verified, as well as low figures of glycemia. Acute fatty liver of pregnancy was diagnosed. After several days hospitalized with an unfavorable clinical course until getting to the critical state, the patient died due to multiple organ dysfunction syndrome.